A descriptive study on the readiness of Filipino Dentists on Cross Border Dental Service - Libo, Ronualdo P.
Globalization is a social process that shapes interdependencies in the world and makes people aware of the local and cross-border connections. Cross-border dental service refers to service rendered by dentists not only to local patients but to patients located in different parts of the globe. This study aims to describe the current status of dental practice in Luzon in accordance with the standards of cross-border dental service, in terms of the physical aspects including infection control, patient documentation, equipment, means of communication, payment system, and professional fee. Purposive sampling was used to conduct a questionnaire-based survey during dental conventions/seminars in Luzon. The survey was conducted in Makati, Baguio, Olangapo, Greenshiils, and Manila where 163 private dentists have participated in the Study. The data that was collected described the current status of dental practice in the Philippines as not yet ready, generally, to be at par with the standards of cross-border dental service specifically in the aspects of infection control, patient documentation, and equipment availability in the dental clinic.